Dynamic Analysis for a Fractional-Order Autonomous Chaotic System - Jiangang Zhang; Juan Nan; Wenju Du; Yandong Chu; Hongwei Luo (Discrete Dynamics in Nature and Society)
We introduce a discretization process to discretize a modified fractional-order optically injected semiconductor lasers model and investigate its dynamical behaviors. More precisely, a sufficient condition for the existence and uniqueness of the solution is obtained, and the necessary and sufficient conditions of stability of the discrete system are investigated. The results show that the system’s fractional parameter has an effect on the stability of the discrete system, and the system has rich dynamic characteristics such as Hopf bifurcation, attractor crisis, and chaotic attractors.